Phenology, distribution and first observation of the larva of the rare stink bug Dybowskyia reticulata (Hemiptera: Heteroptera: Pentatomidae) in Europe - Hemala, V.; Rindoš, Michal (Česká společnost entomologická, 2018)
A new and remarkable record of a 5th instar larva of the extremely rare stink bug Dybowskyia reticulata(Dallas, 1851) is presented from Europe. A chronological overview of all European records of the species is provided and discussed in the context of its Palaearctic distribution, together with an evaluation of the species’ phenology, notes on its biology and modelling of its potential area of current occurrence in Europe. Additionally, an update to the current Slovakian Red List is suggested.
Keywords: Central Europe; Slovakia; Podopinae; phenology; distribution modelling; Red Lis